Evaluation of interfacial toughness function in mixed mode loading - Truong, Do Van; Thanh, Vuong Van (Vietnam Journal of Mechanics, 2012)
Interfacial strength is one of important factors to affect working stability of structures and devices. In order to avoid interfacial cracking, an improved method based on the conventional one is proposed to establish the interfacial toughness function (or the set of the interfacial fracture criteria in mixed-mode loading). By preliminarily analyzing the Brazil nut specimen, the placements of applied load, where pure modes I and II occurred, were determined. Experiment was then conducted on the specimens at the pre-determined placements of applied load. The interfacial toughness function was finally established by an empirical function based on only the critical energy release rates at pure modes I and II. The results showed that the interfacial toughness function was close to that obtained by experimental data and other researches.